Physiological response, endrocrine and performance of broilers under cyclic heat stress - Bueno, João Paulo Rodrigues (2019)
The objective of this study was to evaluate the effects of cyclic heat stress on the serum levels of thyroid hormones (T3 and T4), the thyroid histology, the performance, the temperatures (skin, cloaca, and litter), the feathering and the incidence of pododermatites in two broiler strains (Cobb SlowTM and Hubbard FlexTM), exposed to different heat protocols. It is possible to conclude that exposure to cyclic heat stress for 3 h from day 14 to day 42 did not affect performance, thyroid histology or the serum levels of T3 and T4 and there is no change in feathering and incidence of pododermatites. Cobb Slow™ broilers had the best live weight values at slaughter and higher cloacal temperature. With increasing age, T3 levels decrease and T4 levels increase. The temperatures of the broilers and litter increase as the ambient temperature increases.